If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(2x + -7)(5x + 2) = 0 Reorder the terms: 2x(-7 + 2x)(5x + 2) = 0 Reorder the terms: 2x(-7 + 2x)(2 + 5x) = 0 Multiply (-7 + 2x) * (2 + 5x) 2x(-7(2 + 5x) + 2x * (2 + 5x)) = 0 2x((2 * -7 + 5x * -7) + 2x * (2 + 5x)) = 0 2x((-14 + -35x) + 2x * (2 + 5x)) = 0 2x(-14 + -35x + (2 * 2x + 5x * 2x)) = 0 2x(-14 + -35x + (4x + 10x2)) = 0 Combine like terms: -35x + 4x = -31x 2x(-14 + -31x + 10x2) = 0 (-14 * 2x + -31x * 2x + 10x2 * 2x) = 0 (-28x + -62x2 + 20x3) = 0 Solving -28x + -62x2 + 20x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(-14 + -31x + 10x2) = 0 Factor a trinomial. 2x((-2 + -5x)(7 + -2x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2 + -5x)' equal to zero and attempt to solve: Simplifying -2 + -5x = 0 Solving -2 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = 0 + 2 -5x = 0 + 2 Combine like terms: 0 + 2 = 2 -5x = 2 Divide each side by '-5'. x = -0.4 Simplifying x = -0.4Subproblem 3
Set the factor '(7 + -2x)' equal to zero and attempt to solve: Simplifying 7 + -2x = 0 Solving 7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 0 + -7 -2x = 0 + -7 Combine like terms: 0 + -7 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5Solution
x = {0, -0.4, 3.5}
| 2x^2+23x-312=0 | | 8ln(t+1)=16 | | 2x^2-5x-42= | | (1x)(1x)= | | 9x^2-3x-20= | | 6y^6+36y^5+54y^4= | | 4(5c-1)-6=18c+6 | | 5p-50+10p^2= | | 5p-525+20p^2= | | 7x+4y=9133 | | 9x^2=24x-12 | | -3(z-7)=-2z-3 | | 5+4y=-1 | | p+(p+15)+(180-(2p+15))=180 | | 10z-12-3z+5=0 | | X-3(x-2)=7x-(2x+5) | | 3/4*4= | | (x-3)(x-10)=8 | | -5=-8x+3 | | 7a-45=-10 | | 2t^3-128=0 | | 6x^2=33x-45 | | 15w+12=-3w^2 | | 2x^2-11x-42=-3x | | g(x)=x^2+x-6 | | 7(x+13)-3=2(x+13)+17 | | x^2+11x+18=8 | | 7(x-13)-3=2(x-13)+17 | | 8x^2-6x+24x-18= | | 3(10x-3)=25x+3 | | 2rs^2-8rs-90r= | | 2rs^2-6rs-8r= |